(untitled) (Journal of Health, Population and Nutrition, 2010)
Afghans comprise one of the largest groups of refugees in the world, with the majority living in Pakistan. The objective of this study was to identify commonly-occurring reproductive tract infections (RTIs), describe knowledge of women about RTIs, and assess physical and behavioural factors contributing to the development of RTIs. Afghan women presenting at Basic Health Units in refugee camps in Haripur, Pakistan, with reproductive health-related complaints, were included in the study (n=634). Data collection included implementation of an interviewer-administered questionnaire, along with a physical examination and laboratory tests. A descriptive analysis was conducted first. Qualitative data were coded and analyzed using predetermined themes. Chi-square test was used for determining the possible relationships between a binary outcome and categorical risk factors. Over three-fourths (76.7%) of those who reported to the health clinics with reproductive complaints had an RTI. Nearly half (49.5%) of these women were diagnosed with some form of vaginitis, and 14.7% were diagnosed with clinical suspicion of pelvic inflammatory disease (PID). Women with cervical prolapse (p=0.033) or who cleansed after intercourse (p=0.002) were more likely to have vaginitis. There was a significant difference (p=0.017) in the prevalence of suspected PID among women who used mud only (11.1%), any water (18.8%), and an old cloth or toilet paper (9.8%) for cleansing after defaecation. Specific physical and behavioural contributors to the high prevalence of RTIs in this population were identified, and recommendations to ameliorate these factors are offered. Key words: Maternal health services; Maternal welfare; Morbidity; Pelvic inflammatory disease; Prolapse; Afghanistan DOI: 10.3329/jhpn.v28i5.6159 J HEALTH POPUL NUTR 2010 Oct;28(5):501-508